Combined analysis methods for investigating titanium and nickel surface contamination after plasma deep etching. (11th November 2021) - Ettouri, Rim; Tillocher, Thomas; Lefaucheux, Philippe; Boutaud, Bertrand; Fernandez, Vincent; Fairley, Neal; Cardinaud, Christophe; Girard, Aurélie; Dussart, Rémi
Abstract : Plasma etching techniques can result in damage and contamination of materials, which, if not removed, can interfere with further processing. Therefore, characterisation of the etched surface is necessary to understand the basic mechanisms involved in the etching process and enable process control and cleaning procedures to be developed. A detailed investigation by means of the combined use of scanning electron microscopy coupled with energy‐dispersive X‐ray spectrometry (SEM/EDS), X‐ray photoelectron spectroscopy (XPS) and optical microscopy (OM) has been carried out on deep titanium trenches etched by plasma. This innovative approach has provided a further insight into the microchemical structure of the surface contamination layer on both the titanium and the nickel hard mask surfaces. The described experiments were conducted on 25 to 100‐ μ m wide trenches, first etched in bulk titanium by an optimised C l 2 / S F 6 / O 2 ‐based inductively coupled plasma process, through an electroplated nickel hard mask. The results allow to identify chlorine, fluorine and carbon as the main contaminating agents of the nickel mask and to associate three oxidation states around the etched trenches highlighting certain specific aspects related to the passivation mechanism. These observations reinforce the scientific relevance of the combined use of complementary optical and imaging analytical techniques.